A dinâmica dos circuitos da economia urbana no comércio de confecção de Maracanaú-CE - Queiroz, Emanuelton Antony Noberto de (2023)
In the current period, globalization endows the space with fluidity, science, technique, information and rationality, generating a more intense interaction between the circuits of the economy (Santos, 1979). In this context, the theory of the two circuits of the urban economy is further reinforced as a possibility of apprehending contemporary urban dynamics through communicating vessels (Silveira, 2004). The guiding question is: What are the consequences of the popular clothing trade in the urban economic circuits of Maracanaú?? That said, the general objective is to analyze the socio-spatial impacts of the clothing trade in the circuits of the urban economy of Maracanaú, while the specific objectives are: a) To rescue the formation and development of the economic and socio-spatial structure of Maracanaú; b) To verify the dynamics of the clothing trade in Maracanaú in the lower circuit of the economy c) To understand the interrelations between the upper and lower circuits of the urban economy of Maracanaú through the clothing trade. This research is exploratory, qualitative-quantitative, of the case study type. The research was carried out considering the following stages: a) bibliographic and documentary survey; b) elaboration of thematic newspaper library; c) collection of statistical data from ABRASCE; IBGE; IPECE; ROOT/CAGED; National Household Sample Survey and Monthly Survey of Commerce; d) preparation of maps; e) construction of graphs; f) fieldwork; g) interviews and application of questionnaires; and, h) Creation of the SWOT i) Creation of an online form. Among the fundamental authors in the investigation, we highlight: Santos (1979), Lefebvre (1991; 2016), Pintaudi (1992), Soja (1993), Silveira (2004; 2007), Harvey (2005), Silva (2009), Oliveira (2011), Lencioni (2011), Souza (2013), Muniz (2014; 2022), Vargas (2014), Gomes (2015), Santos (2017), Gonçalves (2017), Eciane Silva (2017), Brenner (2018), Antunes (2019), Gonçalves (2019), Ribeiro (2020).. It is concluded that this trade goes beyond the metropolitan territory and reinvents itself in the midst of the clash with the public power and private interests, with the municipality of Maracanaú in the RMF having a space that also reproduces itself. However, despite its predominance in the lower circuit, big capital advances provoking a metamorphosis in its distribution in space, therefore, the trade of clothing at the same time, which corroborates the right to work in the urban reform, is a challenge in the face of the army of excluded, being denied the right to the city that has become a commodity business city.